A multipurpose immobilized biocatalyst with pectinase, xylanase and cellulase activities - Gupta Munishwar; Sharma Aparna; Dalal Sohel (Chemistry Central Journal, 2007)
Abstract Background The use of immobilized enzymes for catalyzing various biotransformations is now a widely used approach. In recent years, cross-linked enzyme aggregates (CLEAs) have emerged as a novel and versatile biocatalyst design. The present work deals with the preparation of a CLEA from a commercial preparation, Pectinex™ Ultra SP-L, which contains pectinase, xylanase and cellulase activities. The CLEA obtained could be used for any of the enzyme activities. The CLEA was characterized in terms of kinetic parameters, thermal stability and reusability in the context of all the three enzyme activities. Results Complete precipitation of the three enzyme activities was obtained with n-propanol. When resulting precipitates were subjected to cross-linking with 5 mM glutaraldehyde, the three activities initially present (pectinase, xylanase and cellulase) were completely retained after cross-linking. The Vmax/Km values were increased from 11, 75 and 16 to 14, 80 and 19 in case of pectinase, xylanase and cellulase activities respectively. The thermal stability was studied at 50°C, 60°C and 70°C for pectinase, xylanase and cellulase respectively. Half-lives were improved from 17, 22 and 32 minutes to 180, 82 and 91 minutes for pectinase, xylanase and cellulase respectively. All three of the enzymes in CLEA could be reused three times without any loss of activity. Conclusion A single multipurpose biocatalyst has been designed which can be used for carrying out three different and independent reactions; 1) hydrolysis of pectin, 2) hydrolysis of xylan and 3) hydrolysis of cellulose. The preparation is more stable at higher temperatures as compared to the free enzymes.